Single‐Site Metal–Organic Framework and Copper Foil Tandem Catalyst for Highly Selective CO2 Electroreduction to C2H4. Issue 10 (20th December 2022) - Yan, Tingting; Wang, Peng; Sun, Wei‐Yin
Abstract: Tandem catalysis is a promising way to break the limitation of linear scaling relationship for enhancing efficiency, and the desired tandem catalysts for electrochemical CO2 reduction reaction (CO2 RR) are urgent to be developed. Here, a tandem electrocatalyst created by combining Cu foil (CF) with a single‐site Cu(II) metal–organic framework (MOF), named as Cu–MOF–CF, to realize improved electrochemical CO2 RR performance, is reported. The Cu–MOF–CF shows suppression of CH4, great increase in C2 H4 selectivity (48.6%), and partial current density of C2 H4 at −1.11 V versus reversible hydrogen electrode. The outstanding performance of Cu–MOF–CF for CO2 RR results from the improved microenvironment of the Cu active sites that inhibits CH4 production, more CO intermediate produced by single‐site Cu–MOF in situ for CF, and the enlarged active surface area by porous Cu–MOF. This work provides a strategy to combine MOFs with copper‐based electrocatalysts to establish high‐efficiency electrocatalytic CO2 RR. Abstract : A tandem electrocatalyst Cu–MOF–CF by combining Cu foil with Cu–MOF is developed to realize improved C2 H4 product selectivity for CO2 RR, which is attributed to the improved microenvironment of the Cu active sites that inhibits CH4 production, more CO intermediate produced by single‐site Cu–MOF for CF, and the enlarged active surface area by porous Cu–MOF.